Active management, value investing and pension fund performance - Luis Otero-González; Pablo Durán-Santomil; Rubén Lado-Sestayo; Milagros Vivel-Búa (European Journal of Management and Business Economics (EJM&BE), 2021)
Purpose - This paper analyses whether the active management and the fundamentals of the pension fund allow products that beat their peers to be identified in terms of risk-adjusted performance. Design/methodology/approach - The sample is composed of all the pension funds active in the period 2000 to 2017 investing in the Eurozone. What this means is that a greater similarity is guaranteed in terms of benchmark, assets available for investment and currency. All the data have been retrieved from the Morningstar Direct database. Findings - The paper reveals that the degree of concentration and value for money are important determinants of performance. In this sense, the strategies of investing in concentrated portfolios that differ from the benchmark and with undervalued assets in terms of price earnings ratio (PER)-return on assets (ROA) achieve better results. Originality/value - This is one of the few papers that shows the effect of active management and value investing strategies' on the performance of pension funds.
Keywords: 650; Active management; Individual pension funds; Performance; Value investing